Chapter 5 Didactic audio description and didactic free commentary - TALAVAN, NOA (Taylor & Francis, 2024)
This chapter will focus on didactic Audio Description (AD) and didactic free commentary. Firstly, it will provide the reader with an overview of the main types of didactic AD (DAD) and didactic free-commentary (DFC), differentiating between intersemiotic for both modes as well as intralingual, and interlingual for free commentary. Afterwards, it will present how didactic AD and didactic free commentary can foster communicative skills mainly in terms of audiovisual production and mediation, and audiovisual reception to a certain extent. Guidelines to implement DAD and DFC will be explained in detail together with a sample of assessment rubrics which can be adapted according to the learning contexts. Finally, sample lesson plans on both DAT modes will be presented.